?f -Lacunary Statistical Boundedness of Order ? for Sequences of Fuzzy Numbers - Altinok, Hifsi; Kasap, Mithat (Univ Craiova, 2023)
In the present paper, we introduce the concept of Delta f -lacunary statistical bound-edness of order beta with respect to a modulus function f for sequences of fuzzy numbers and give some relations between Delta f -lacunary statistical boundedness of order beta and Delta f -statistical boundedness with respect to a modulus function f with the help of many examples and figures. Furthermore, we study some properties like solidity, symmetricity, etc.
Keywords: Statistical convergence; statistical boundedness; lacunary sequence; modulus function; fuzzy sequence; difference operator